Effect of histone deacetylase and DNA methyltransferase inhibitors on the expression of the androgen receptor gene in androgen-independent prostate cancer cell lines - Fialova, Barbora; Smesny Trtkova, Katerina; Paskova, Lenka; Langova, Katerina; Kolar, Zdenek (Oncology reports, 2013)
Androgen receptor (AR) expression in prostate cancer (CaP) cells varies due to the multiple changes including epigenetic modifications such as DNA methylation and histone deacetylation. DNA methyltransferase and histone deacetylase inhibitors are promising for the treatment of CaP. The aim of our study was to analyze the 5-aza-2'-deoxycytidine (Aza‑dC) and sodium butyrate (NaB) effects on CaP cells with modified AR gene expression. The androgen-independent human prostate cancer cell lines PC3 (lacking a functional AR) and DU145 (strongly limited expression due to methylations in the AR gene) were used. PCR of bisulfite-modified DNA and RT-PCR with bisulfite-sequencing were used for AR gene analysis of DU145 and PC3 cells following their treatment with Aza-dC and/or NaB. Re-acetylated histones around the AR gene were detected by conventional PCR of immunoprecipitated DNA obtained from treated cells. In both cell lines without the AR expression, the combined treatment was followed with significant decrease of cell viability. The co-treatment of DU145 cells caused site-specific demethylation in the AR promoter region followed by gene re-expression and increased acetylation in histones H3 and H4. The co-treatment with Aza-dC and NaB was the most effective in demethylation and re-expression of the AR gene. In the AR gene promoter, the location and density of deme-thylated CpGs indicated the existence of distinct promoter hot spot that could be a target of AR gene inactivation therapy of CaP patients during androgen deprivation.
Keywords: Histone Deacetylases; 5' nepřekládaná oblast; Androgens; Prostatic Neoplasms, Castration-Resistant; azacytidin; methyltransferasy; Acetylation; Cell Line, Tumor; inhibitory histondeacetylas; DNA; lidé; Butyric Acid; histondeacetylasy; Azacitidine; Methyltransferases; kyselina máselná; metylace DNA; Histone Deacetylase Inhibitors; Male; 5' Untranslated Regions; DNA Methylation; histony; nádory prostaty rezistentní na kastraci; Histones; Cell Survival; promotorové oblasti (genetika); mužské pohlaví; Promoter Regions, Genetic; viabilita buněk; Receptors, Androgen; androgenní receptory; androgeny; nádorové buněčné linie; acetylace; Humans